Strategies Of Teaching Reading To Student At The Second Year Of SMA Muhammadiyah 1 Surakarta - Dhani B, Shenly Nuari (2012)
This research aims at finding out the strategies of teaching reading to student at the second year and to find problems faced by the teacher and problems solving of teaching reading in SMA Muhammadiyah 1 Surakarta. The research involved the English teacher and students of the second year as the subject of the study. This research is a qualitative research. To collect the data the writer used observation, interview, and document. The data were analyzed to find out the strategies in teaching reading used by the teacher, comparing the result of interview with the situation in the class, making note whether in classroom, concluding the strategies used by the teacher appropriate or not with the components of strategies in teaching reading by Slavin, making conclusion based on the result of analysis and giving some suggestions. The result of the analysis shows that (1) the teacher in SMA Muhammadiyah 1 Surakarta used STAD and Group Investigation (GI) in teaching reading strategies. The strategies in teaching reading used by the teacher are appropriate with components of strategies in teaching reading by Slavin in giving material to the students. (2) There are six problem faced by the teacher: one of them is the teacher gets difficulties in controlling the students in the class, the students have less motivation in learning English, the teacher has a limited time, the students have limited vocabulary, the students have not clear pronounciation, and different ability among of the students. (3) Then, there are six problem solving by the teacher: the teacher walk around the class when teaching learning process run to control the class, the teacher gives interesting materials to motivate the students, the teacher change time in the next meeting, the teacher asks students to summariez text by their own words, makes direct controling to the student's error in pronountiation, the teacher give remediation for the students who have poor score until they get a standard score.